Effect of Cash Ratio, Total Asset Turn over and Debt to Equity Ratio on Net Profit Margin in Porselain, Ceramic and Glass listed on the Indonesia Stock Exchange for the 2015-2019 Period - Siregar, Muhammad Yamin; Nasution, Silvia Octrianti (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of Cash Ratio, Total Asset Turn Over, Debt to Equity Ratio on Net Profit Margin in Porcelain, Ceramic and Glass Companies Listed on the Indonesia Stock Exchange. This type of research is associative. The data used are secondary data and the method used is multiple linear regression analysis of panel data with the help of Eviews9 and Eviews10 programs. The population in this study were 8 companies of porcelain, ceramic and glass companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample in this study amounted to 4 companies. Partially, the Cash Ratio has a significant effect on the Net Profit Margin of Porcelain, Ceramic and Glass Companies Listed on the Indonesia Stock Exchange. Partially Total Asset Turn Over does not have a positive and significant effect on the Net Profit Margin of Porcelain, Ceramic and Glass Companies Listed on the Indonesia Stock Exchange. Partially the Debt to Equity Ratio (DER) has a significant negative effect on Net Profit Margin (NPM). Simultaneously CR, TATO and DER have a positive and significant effect on NPM. The coefficient of determination (R2) is 0.808818, so it can be concluded that 80.88% of NPM is influenced by CR, TATO and DER and the remaining 19.12% is influenced by other variables not examined in this study.